Pole piece plasticizer for lithium battery and preparation method of pole piece plasticizer
By designing a lithium battery electrode plasticizer with a structure of R1O(C2H4O)m(C3H6O)n-C(O)-R2, the existing plasticizers have been solved, with poor stability, high addition amount and poor versatility. It has achieved good plasticization stability, low addition amount and strong versatility, and is suitable for the negative and positive electrode sheets of lithium batteries.
Patent Information
- Application Number
- CN202411579556.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-18
AI Technical Summary
Existing lithium battery electrode plasticizers have poor stability, high addition amount, and poor versatility, making it difficult to meet the needs of high energy density and good performance.
A electrode sheet plasticizer for lithium batteries with a structure of R1O(C2H4O)m(C3H6O)n-C(O)-R2 is provided, which destroys hydrogen bonding in the electrode sheet by small molecule segments to improve the flexibility and versatility of the electrode sheet.
This plasticizer has the advantages of good plasticization stability, low addition amount and strong versatility. It can show good performance in both the negative and positive electrode sheets, and does not affect battery performance while replacing high-boiling point solvents.
Smart Images

Figure BDA0005122675220000021 
Figure BDA0005122675220000071 
Figure BDA0005122675220000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a pole piece plasticizer for lithium batteries and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are rechargeable batteries used in consumer devices such as smartphones and laptops, power tools such as electric cars and electric boats, and energy storage devices. They are composed of positive electrode materials, negative electrode materials, separators, and non-aqueous electrolyte solutions. Lithium-ion batteries charge and discharge by reversibly inserting and removing lithium ions from the crystal structure of the negative electrode material. Lithium-ion batteries have the advantages of high energy density, light weight, and no "memory effect", and are widely used in various electronic devices, transportation, and other fields.
[0003] In order to pursue higher energy density, lithium-ion batteries generally start from various aspects of battery cell design: such as increasing the gram capacity of active materials, increasing the mass proportion of active materials, lithium supplementation design, thick coating (reducing the proportion of inactive components such as diaphragms and substrates), etc. Among them, from the perspective of positive / negative pole pieces, the goal of high energy density can be achieved by increasing the compaction density of the pole pieces and increasing the thickness of the pole pieces. However, this will bring some problems, such as easy cracking of the pole pieces, difficulty in electrolyte infiltration, and insufficient electrolyte retention of the pole pieces.
[0004] At present, some plasticizers can effectively improve the above problems. Plasticizers, also called anti-cracking agents, can be used to enhance the flexibility and plasticity of the pole piece and reduce the cracking of the pole piece. The application of negative electrode plasticizers has the following mechanism: The development direction of plasticizers is generally small molecule VOC, non-water-soluble solvents, polyester polymers, polyurethane polymers, polyether polymers, and polycarboxylate polymers. The types of plasticizers commonly used in negative electrode slurry are as follows: N-methylpyrrolidone (NMP), isopropyl alcohol (IPA), ethylene carbonate (EC) and 1,3-butanediol. Among them, NMP is a solvent normally used in the positive electrode. Its surface tension in water is about 40mN / m. It can improve the cracking of the pole piece to a certain extent, but it has certain toxicity when used in the negative electrode, and the concentration of the volatilized components is low and difficult to recover; IPA has a lower surface tension, and theoretically can achieve a thicker pole piece coating, but IPA is a flammable liquid and the addition amount is high, and the evaporation process is dangerous; EC is a common solvent in the electrolyte, which can also improve cracking and achieve thick coating, but the addition amount of EC is high, and the freezing point is only 38°C. After evaporation, it will solidify on the ceiling, which is dangerous and difficult to post-process. 1,3-Butanediol is a plasticizer used more in the negative electrode to improve cracking and achieve thick coating. Its advantages are low cost, good effect, and it is a volatile plasticizer. It does not occupy the proportion of solid components and can flexibly adjust the addition amount. Its disadvantage is that the addition amount is high and it is difficult to completely volatilize. Generally, there will be hundreds of ppm (one millionth) of residues, which has a great impact on the performance of the battery.
[0005] CN115975171A discloses a polyether plasticizer and its application in the field of lithium battery preparation, wherein the structure is R 1 O(C 2 H 4 O) m (C 3 H 6 O) n -C(O)-R 2 , where R 1 For structures such as phenyl, R 2 C 8 -C 18 The plasticizer solves the problem that the lithium ion battery positive electrode slurry has insufficient toughness and flexibility when thickly coated, which leads to easy leakage or cracking of the electrode sheet when it is wound and folded.
[0006] Some of the plasticizers disclosed so far cannot meet better performance requirements and need further development. Summary of the invention
[0007] The technical problem to be solved by the present invention is that the plasticizer in the prior art has poor stability, high addition amount and low versatility.
[0008] In order to solve the above technical problems, in the first aspect, the present invention provides a lithium battery pole piece plasticizer, the structure of the lithium battery pole piece plasticizer is shown in Formula I:
[0009]
[0010] Among them, R 1 for Wherein A is selected from H, hydroxyl, C 1 ~C 20 Alkyl, C 1 ~C 20 Any one of the hydrocarbon groups; R 2 is any one of hydrogen, methyl, ethyl or phenyl;
[0011] R 3 is hydrogen, methyl, ethyl, Any one of a phosphate group, a sulfonic acid group, a sulfate group, a phosphate, a sulfonate, a sulfate, an organic amine sulfate salt, an organic amine sulfonate salt, and an organic amine phosphoric acid salt;
[0012] x and y are integers between 0 and 15, and the sum of x and y is an integer between 1 and 15. For example, when the sum of x and y is 1, x is 0 and y is 1, or x is 1 and y is 0.
[0013] In the present invention, the wavy line in the above structural formula represents the connecting bond of the substituent in the structure of Formula I. The substitution position of A can be any position on the benzene ring except the substituent, and can also be substituted at multiple positions of the benzene ring at the same time. 1 ~C 20 Alkyl or C 1 ~C 20 When the hydrocarbon group is a hydrocarbon group, it may have various types of branched structures; for example, the structure of A may be etc.
[0015] Specifically, R 1 It may be benzoic acid, o-hydroxybenzoic acid, m-hydroxybenzoic acid, p-hydroxybenzoic acid, o-methylbenzoic acid, m-methylbenzoic acid, p-methylbenzoic acid, o-hydroxybenzyl alcohol, m-hydroxybenzyl alcohol, p-hydroxybenzyl alcohol, o-methylbenzyl alcohol, m-methylbenzyl alcohol, p-methylbenzyl alcohol, phenol, catechol, resorcinol, hydroquinone, o-methylphenol, m-methylphenol, p-methylphenol, β-naphthol, aniline, o-methylaniline or m-methylaniline, and the like.
[0016] R 3The phosphate in the salt may be sodium phosphate, potassium phosphate, ammonium phosphate, etc., the sulfonate may be potassium sulfonate, sodium sulfonate, ammonium sulfonate, etc., the sulfate may be potassium sulfate, sodium sulfate, ammonium sulfate, etc. The organic amine in the organic amine sulfate salt, organic amine sulfonate salt, organic amine phosphoric acid salt may be a primary amine, a secondary amine, etc.
[0017] The plasticizer provided by the present invention has the characteristics of good plasticizing stability, low addition amount, good versatility, etc., and can be applied to negative electrode sheets and positive electrode sheets. In the negative electrode sheet, it destroys the strong hydrogen bond effect between the carboxymethyl cellulose segments in the negative electrode sheet through small molecular segments. At the same time, due to the structural design and short chain length, this "hydrogen bond destruction" effect will continue in pulping, coating drying, rolling and post-processing. Among them, the addition amount of 0.1% to 0.3% can replace the addition amount of 1% to 4% of the high boiling point solvent, and it is more compatible with the electrolyte and has no effect on the battery performance.
[0018] R 1 for R 2 is methyl, R 3 is hydrogen or phosphate, x is 3, and y is 3.
[0019] In the present invention, the structure formed by the above groups is preferred as a plasticizer, which has a better effect. This is because R 1 It is a hydrophobic group and has no group that forms hydrogen bonds. After the existing hydrogen bonds are destroyed at the other end of the plasticizer, R 1 This end achieves the goal of plasticization because it cannot form hydrogen bonds again.
[0020] In a second aspect, the present invention provides a method for preparing the pole piece plasticizer for lithium batteries according to the first aspect, the preparation method comprising:
[0021] (1) With epoxide in the presence of a catalyst, heating reaction to obtain a reaction intermediate;
[0022] (2) reacting the reaction intermediate with a modifier I, and then reacting with an optional modifier II to obtain the electrode plasticizer for a lithium battery.
[0023] Middle, that is, R 1 The wavy line in the substituent is replaced by a hydrogen atom connected to R 1 Participate in the preparation process of the reaction.
[0024] Preferably, the epoxide in step (1) comprises any one of ethylene oxide, propylene oxide, butylene oxide or styrene oxide, or a combination of at least two thereof.
[0025] Preferably, in step (1) The molar ratio of epoxide to 1:1 is 1:1-15.
[0026] Preferably, the catalyst in step (1) comprises any one of sodium hydroxide, potassium hydroxide, sodium methoxide, potassium methoxide, sodium ethoxide, potassium ethoxide or boron trifluoride, or a combination of two or more thereof.
[0027] Preferably, the temperature of the heating reaction in step (1) is 70-200°C, for example, 70°C, 100°C, 150°C, 180°C or 200°C, etc., preferably 120-150°C.
[0028] Preferably, the heating reaction time in step (1) is 2 to 12 hours, for example, it can be 2 hours, 4 hours, 5 hours, 8 hours, 10 hours or 12 hours.
[0029] Preferably, the modifier I in step (2) comprises any one of methyl chloride, ethyl chloride, acetic anhydride, phosphorus pentoxide, aminosulfonic acid, sulfonic acid or sulfur trioxide, or a combination of at least two thereof.
[0030] Preferably, the modifier II in step (2) comprises any one of alkali metal oxides, alkali metal hydroxides, alkaline earth metal oxides, alkaline earth metal hydroxides, monoethanolamine, diethanolamine, triethanolamine, isopropylamine or diisobutylamine, or a combination of at least two thereof.
[0031] In a third aspect, the present invention provides a positive electrode slurry for a lithium-ion battery, wherein the positive electrode slurry for a lithium-ion battery comprises the pole piece plasticizer for a lithium battery as described in the first aspect, a positive electrode active material, a conductive agent, a binder and a solvent.
[0032] Preferably, the positive electrode active material comprises lithium nickel cobalt manganese oxide LiNi p Co q Mn (1-p-q) O 2 , lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, and lithium iron cobalt phosphate, any one or a combination of at least two of them.
[0033] Preferably, the conductive agent includes any one of conductive carbon black, conductive graphite, acetylene black, Ketjen black, graphene, and carbon nanotubes, or a combination of at least two of them.
[0034] Preferably, the binder includes any one of vinylidene fluoride homopolymer, vinylidene fluoride copolymer, polyhexafluoropropylene, or a combination of at least two thereof.
[0035] Preferably, the solvent is N-methylpyrrolidone.
[0036] In a fourth aspect, the present invention provides a lithium-ion battery positive electrode plate, wherein the lithium-ion battery positive electrode plate comprises the lithium-ion battery positive electrode slurry described in the third aspect.
[0037] In a fifth aspect, the present invention provides a negative electrode slurry for a lithium ion battery, wherein the negative electrode slurry for a lithium ion battery comprises the pole piece plasticizer for a lithium battery as described in the first aspect, a negative electrode active material, a conductive agent, a binder and a solvent.
[0038] Preferably, the negative electrode active material includes any one of graphite, hard carbon or silicon oxide, or a combination of at least two of them.
[0039] Preferably, the conductive agent includes any one of conductive carbon black, conductive graphite, acetylene black, Ketjen black, graphene, and carbon nanotubes, or a combination of at least two of them.
[0040] Preferably, the binder includes any one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium polyacrylate, lithium polyacrylate, polyacrylamide, acrylic acid-acrylonitrile copolymer, butadiene-styrene emulsion, styrene-acrylic acid emulsion, or a combination of at least two thereof.
[0041] Preferably, the solvent is water.
[0042] In a sixth aspect, the present invention provides a negative electrode plate for a lithium-ion battery, wherein the negative electrode plate for a lithium-ion battery comprises the negative electrode slurry for a lithium-ion battery according to the fifth aspect.
[0043] In addition to being used in negative electrode plates, the plasticizer provided by the present invention can also be used for plasticizing positive electrode plates. Through a specific structural design, the non-volatile plasticizer of the present invention can be dissolved in water or in NMP, and has a common basis for positive and negative electrodes. Secondly, the mechanism of positive electrode plasticization is similar to that of the negative electrode. It is also that the oligomer plasticizer destroys the strong HF hydrogen bonding between the positive electrode such as polyvinylidene fluoride binder through small molecule segments, thereby improving the flexibility of the pole piece and enhancing the operability of the pole piece manufacturing process.
[0044] The implementation of the present invention has the following beneficial effects:
[0045] The plasticizer provided by the present invention has the advantages of good plasticizing effect, good flexibility improvement, simple preparation process and controllable structure, and is a universal plasticizer for water and oil. It can be used for plasticizing positive electrode sheets of lithium batteries such as nickel cobalt manganese oxide, lithium iron manganese phosphate, lithium iron phosphate, lithium cobalt oxide, and lithium manganese oxide, and can also be used for plasticizing negative electrode sheets such as graphite, hard carbon, and silicon oxide / graphite mixture. It is a universal plasticizer. Compared with existing plasticizers, it has a wider range of use, better effects, and good application prospects and application value. DETAILED DESCRIPTION
[0046] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0047] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0048] Positive Electrode Example
[0049] Table 1 below shows the structural formula of the lithium battery pole piece plasticizer used in the examples:
[0050] Table 1
[0051]
[0052]
[0053] Example:
[0054] The specific preparation steps of the lithium battery positive electrode slurry of Examples AH and Control Group 1 are as follows:
[0055] 1) 1.64 g PVDF and 40.50 g NMP solvent were mixed and stirred to obtain a glue solution with a certain solid content ①;
[0056] 2) Add plasticizers AH in Table 1 to the glue solution ① respectively and stir evenly to obtain glue solution ②, the added weight of the plasticizer is 0.44 g;
[0057] 3) Add 2.74 g of conductive carbon black to the glue solution ② to obtain slurry ①;
[0058] 4) adding 104.68 g of positive electrode active material lithium nickel cobalt manganese oxide into slurry ① to obtain positive electrode slurry;
[0059] 5) The positive electrode slurries with added plasticizer AH are experimental groups 1-8.
[0060] The specific preparation steps of the lithium battery positive electrode slurry of the control group 1 without using plasticizer are as follows:
[0061] 1) 1.64 g PVDF and 40.50 g NMP solvent were mixed and stirred to obtain a glue solution with a certain solid content ①;
[0062] 2) adding 2.74 g of conductive carbon black into the glue solution ① to obtain slurry ①;
[0063] 4) adding 105.12 g of positive electrode active material lithium nickel cobalt manganese oxide into slurry ① to obtain positive electrode slurry;
[0064] 5) The positive electrode slurry without using a plasticizer is the control group 1.
[0065] Slurry testing:
[0066] An MCR302E rheometer from Anton Paar was used to test the rheological curves of the positive electrode slurries of experimental groups 1-8 and control group 1 at a shear rate of 0.1-10001 / s, and the viscosity at a shear rate of 1 1 / s was taken as the comparative viscosity.
[0067] The coating process of the positive electrode sheet is as follows:
[0068] The electrode slurry was evenly coated on the carbon-coated aluminum foil (single-sided coating) using a Kejing MSK-AFA-ES200 infrared drying flat plate coating machine at a coating speed of 30 cm / min. The carbon-coated aluminum foil consisted of an aluminum foil with a thickness of 10 μm and a carbon material coating with a thickness of 2 μm on one side. The coating weight was 21 mg / cm 2 ; Bake at 120° C. for 1 hour to remove the solvent, and the positive electrode plate in the embodiment of the present invention can be obtained.
[0069] The rolling process of the positive electrode sheet is as follows:
[0070] At a coating speed of 0.5m / min, the positive electrode sheet was rolled evenly to 3.4g / cm by using a Kejing MSK-2300A hydraulic balanced electric roller press and adjusting the pressure and roller gap. 3 The compaction density can be obtained to obtain the positive electrode sheet after rolling.
[0071] Folding light leakage test:
[0072] Fold the rolled positive electrode sheet in half, use a 2kg roller to roll the folded sheet 5 times, then flatten the positive electrode sheet, observe whether the fold is leaking or broken, repeat the rolling operation until the fold leaks, and take 5 times as 1 fold, and record the number of folds. Test each group 3 times in parallel and take the average value.
[0073] The electrode resistance test process is as follows:
[0074] The rolled positive electrode plate was folded in half and cut into a size of 10cm*6cm. The plate resistance was tested using a BER1050 plate resistance meter from Yuanneng Technology. Ten points were tested for each set of plates and the average value was taken.
[0075] Pole piece adhesion test:
[0076] The rolled positive electrode sheet was folded in half and cut into a size of 15cm*2.5cm, and then the cut sheet was pasted on a steel plate with a 2cm wide double-sided tape, and the double-sided tape was completely covered. The positive electrode sheet bonding strength was tested using a Kejian KJ-1069A tensile testing machine in 90° peeling mode. Three parallel samples were tested for each group of sheets, and the average value was taken. The results are shown in Table 2 below.
[0077] Table 2
[0078]
[0079] According to the test results of Examples AH, the plasticizer of the present invention has little effect on the viscosity of the formed positive electrode active material nickel cobalt lithium manganese oxide slurry, the formed electrode sheet bonding force is not deteriorated, and the electrode sheet has higher flexibility.
[0080] Negative Electrode Example
[0081] Table 3 below shows the structural formula of the lithium battery pole piece plasticizer used in the examples:
[0082] Table 3
[0083]
[0084] Negative electrode embodiment:
[0085] The specific preparation steps of the lithium battery negative electrode slurry of the control group 3 using the plasticizer of Example JP and 1,3-butanediol are as follows:
[0086] 1) Mix 0.81g CMC and 80.48g deionized water and stir evenly to obtain a glue solution with a certain solid content③;
[0087] 2) Add the plasticizers JP in Table 2 to the adhesive solution ③ and stir evenly to obtain adhesive solution ④, with the added weight of the plasticizer being 0.20 g;
[0088] 3) adding 0.68 g of conductive carbon black into the glue solution ④ to obtain slurry ②;
[0089] 4) adding 64.46 g of negative electrode active material graphite to slurry ② to obtain slurry ③;
[0090] 5) Add 3.38 g of SBR emulsion to slurry ③ to obtain negative electrode slurry;
[0091] 6) The negative electrode slurries with plasticizer JP added were experimental groups 9-15, the group without plasticizer was control group 2, and the group with control plasticizer was control group 3.
[0092] The specific preparation steps of the lithium battery negative electrode slurry of the control group 2 without using a plasticizer are as follows:
[0093] 1) Mix 0.81g CMC and 80.48g deionized water and stir evenly to obtain a glue solution with a certain solid content⑤;
[0094] 2) Add 0.68 g of conductive carbon black into the glue solution ⑤ and disperse evenly to obtain slurry ④;
[0095] 4) adding 64.67 g of negative electrode active material graphite to slurry ④ and dispersing evenly to obtain slurry ⑤;
[0096] 5) adding 3.38 g of SBR emulsion to slurry ⑤ and mixing to obtain negative electrode slurry;
[0097] 6) The group without plasticizer is control group 2.
[0098] The specific preparation steps of the lithium battery negative electrode slurry of the control group 3 using 1,3-butanediol as a plasticizer are as follows:
[0099] 1) Mix 0.81g CMC and 79.80g deionized water and stir evenly to obtain a glue solution with a certain solid content ⑥;
[0100] 2) Add 0.68 g of 1,3-butanediol to the glue solution ⑥ and mix well to obtain glue solution ⑦;
[0101] 3) Add 0.68 g of conductive carbon black into the glue solution ⑦ and disperse evenly to obtain slurry ⑥;
[0102] 4) adding 64.67 g of negative electrode active material graphite to slurry ⑥ and dispersing the mixture evenly to obtain slurry ⑦;
[0103] 5) adding 3.38 g of SBR emulsion to slurry ⑦ and mixing to obtain negative electrode slurry;
[0104] 6) The group using 1,3-butanediol as a plasticizer is designated as Control Group 3.
[0105] Slurry testing:
[0106] Anton Paar's MCR302E rheometer was used to test the rheological curves of the negative electrode slurries of experimental groups 9-15, control group 2, and control group 3 at a shear rate of 0.1-1000 1 / s, and the viscosity at a shear rate of 1 1 / s was taken as the comparison viscosity.
[0107] The coating process of the pole piece is as follows:
[0108] The electrode slurry was evenly coated on a copper foil with a thickness of 10 μm (single-sided coating) at a coating speed of 30 cm / min using a Kejing MSK-AFA-ES200 infrared drying flat plate coating machine. The coating weight was 13 mg / cm 2; Bake at 120° C. for 14 minutes to remove the solvent, and the negative electrode plate in the embodiment of the present invention can be obtained.
[0109] The rolling process of the pole piece is as follows:
[0110] The negative electrode sheet is rolled at a coating speed of 0.5 m / min using a Kejing MSK-2300A hydraulically balanced electric roller machine. By adjusting the pressure and roller gap, the negative electrode sheet is evenly rolled to a compaction density of 1.6 g / cm3 to obtain the rolled negative electrode sheet.
[0111] Pole curl height test:
[0112] The coated negative electrode plates were naturally dried at room temperature, and the dried plates were cut into small pieces of 2.7*2.7 cm. The cut pieces were then placed on a heating plate at 115°C. After waiting for 30 seconds, the curling height of the plates was measured and recorded. Each group was tested three times in parallel and the average value was taken.
[0113] Pole piece adhesion test:
[0114] The rolled negative electrode sheet was folded in half and cut into a size of 15cm*2.5cm, and then the cut sheet was pasted on a steel plate with a 2cm wide double-sided tape, and the double-sided tape was completely covered. The adhesion of the negative electrode sheet was tested using the 180° peeling mode of the Kejian KJ-1069A tensile testing machine. Three parallel samples were tested for each group of sheets, and the average value was taken. The test results are shown in Table 4 below.
[0115] Table 4
[0116]
[0117] It can be seen from the above data that when the plasticizer provided by the present invention is applied to the negative electrode, the curling height is lower and the bonding force is lower, which shows that the use of the plasticizer of the present invention can significantly improve the flexibility of the electrode sheet, but at the same time, because the plasticizer of the present invention reduces the hydrogen bonding effect in the binder CMC, the bonding force will be reduced accordingly.
[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium battery pole piece plasticizer, characterized in that: The structure of the lithium battery pole piece plasticizer is shown in Formula I: Among them, R1 is Wherein A is selected from H, hydroxyl, C1~C 20 Alkyl, C1~C 20 Any of the hydrocarbon groups; R2 is any one of hydrogen, methyl, ethyl or phenyl; R3 is hydrogen, methyl, ethyl, Any one of a phosphate group, a sulfonic acid group, a sulfate group, a phosphate, a sulfonate, a sulfate, an organic amine sulfate salt, an organic amine sulfonate salt, and an organic amine phosphoric acid salt; x and y are integers between 0 and 15, and the sum of x and y is an integer between 1 and 15.
2. The lithium battery pole piece plasticizer according to claim 1, characterized in that: R1 is R2 is a methyl group, R3 is a hydrogen or phosphate group, x is 3, and y is 3.
3. The method for preparing a pole piece plasticizer for a lithium battery according to claim 1 or 2, characterized in that: The preparation method comprises: (1) With epoxide in the presence of a catalyst, heating reaction to obtain a reaction intermediate; (2) reacting the reaction intermediate with a modifier I, and then reacting with an optional modifier II to obtain the electrode plasticizer for a lithium battery.
4. The preparation method according to claim 3, characterized in that: The epoxide in step (1) includes any one of ethylene oxide, propylene oxide, butylene oxide or styrene oxide, or a combination of at least two thereof; Preferably, in step (1) The molar ratio with epoxide is 1:1 to 15; Preferably, the catalyst in step (1) comprises any one or a combination of two or more of sodium hydroxide, potassium hydroxide, sodium methoxide, potassium methoxide, sodium ethoxide, potassium ethoxide or boron trifluoride; Preferably, the temperature of the heating reaction in step (1) is 70 to 200° C.; Preferably, the heating reaction time in step (1) is 2 to 12 hours; Preferably, the modifier I in step (2) comprises any one or a combination of at least two of methyl chloride, ethyl chloride, acetic anhydride, phosphorus pentoxide, aminosulfonic acid, sulfonic acid or sulfur trioxide; Preferably, the modifier II in step (2) comprises any one of alkali metal oxides, alkali metal hydroxides, alkaline earth metal oxides, alkaline earth metal hydroxides, monoethanolamine, diethanolamine, triethanolamine, isopropylamine or diisobutylamine, or a combination of at least two thereof.
5. A positive electrode slurry for a lithium ion battery, characterized in that: The lithium-ion battery positive electrode slurry comprises the lithium battery pole piece plasticizer as claimed in claim 1 or 2, a positive electrode active material, a conductive agent, a binder and a solvent.
6. The positive electrode slurry for lithium-ion batteries according to claim 5, characterized in that: The positive electrode active material includes lithium nickel cobalt manganese oxide LiNi p Co q Mn (1-p-q) Any one of O2, lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, and lithium iron cobalt phosphate, or a combination of at least two thereof; Preferably, the conductive agent includes any one of conductive carbon black, conductive graphite, acetylene black, Ketjen black, graphene, and carbon nanotubes, or a combination of at least two thereof; Preferably, the binder comprises any one of vinylidene fluoride homopolymer, copolymer, polyhexafluoropropylene or a combination of at least two thereof; Preferably, the solvent is N-methylpyrrolidone.
7. A positive electrode plate for a lithium-ion battery, characterized in that: The lithium-ion battery positive electrode plate comprises the lithium-ion battery positive electrode slurry according to claim 5 or 6.
8. A negative electrode slurry for a lithium ion battery, characterized in that: The negative electrode slurry for lithium-ion batteries comprises the pole piece plasticizer for lithium batteries as claimed in claim 1 or 2, a negative electrode active material, a conductive agent, a binder and a solvent.
9. The positive electrode slurry for lithium-ion batteries according to claim 8, characterized in that: The negative electrode active material includes any one of graphite, hard carbon or silicon oxide or a combination of at least two thereof; Preferably, the conductive agent includes any one of conductive carbon black, conductive graphite, acetylene black, Ketjen black, graphene, and carbon nanotubes, or a combination of at least two thereof; Preferably, the binder includes any one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium polyacrylate, lithium polyacrylate, polyacrylamide, acrylic acid-acrylonitrile copolymer, butadiene-styrene emulsion, styrene-acrylic acid emulsion, or a combination of at least two thereof; Preferably, the solvent is water.
10. A negative electrode plate for a lithium ion battery, characterized in that: The lithium ion battery negative electrode plate comprises the lithium ion battery negative electrode slurry according to claim 8 or 9.
Citation Information
Cited By
Polypropylene fiber short fiber for automobile wheel cover and preparation method of polypropylene fiber short fiber
CN122013342A